Phytoremediation in Constructed Wetlands Using Genjer to Reduce COD, TDS, and Phosphate - Erlina Kurnianingtyas; Pasu Nio Lya Panggabean; Mutiara Fajar; Nur Faizaturrohmah (Universitas Andalas, 2026)
The increase in laundry service activities in Indonesia has an impact on the high water pollution due to the disposal of laundry waste containing chemicals such as COD, TDS, and Phosphate. Laundry waste, which is discharged directly into the environment without treatment, can lead to eutrophication, deterioration of water quality, and the death of aquatic biota. Phytoremediation with a constructed wetland system using genjer plants (Limnocharis flava) was chosen as an environmentally friendly, and low-cost treatment alternative. This study aims to analyze the effectiveness of reducing COD, TDS, and Phosphate levels of laundry waste with genjer plants in the constructed wetland system, as well as to analyze the relationship between the 0, 4th, 8th and 12th day stay time on the reduction of parameters before and after treatment. Preliminary experiments used a control reactor (without plants) and a treatment reactor (10 plants). The results of this study showed the ability to set aside the largest removal in the treatment reactor at COD levels of 88,147%, TDS of 12,776% and phosphate of 14,911% on day 12.. This shows that the constructed wetland method is relatively effective to be applied as laundry waste treatment.